Spaced TiO2 Nanotubes Enable Optimized Pt Atomic Layer Deposition for Efficient Photocatalytic H2 Generation - Ozkan, Selda; Yoo, JeongEun; Nguyen, Nhat Truong; Mohajernia, Shiva; Zazpe, Raul; Prikryl, Jan; Macak, Jan M; Schmuki, Patrik (ChemistryOpen, 2018)
In the present work, we report the use of TiO2 nanotube (NT) layers with a regular intertube spacing that are decorated by Pt nanoparticles through the atomic layer deposition (ALD) of Pt. These Pt-decorated spaced (SP) TiO2 NTs are subsequently explored for photocatalytic H2 evolution and are compared to classical close-packed (CP) TiO2 NTs that are also decorated with various amounts of Pt by using ALD. On both tube types, by varying the number of ALD cycles, Pt nanoparticles of different sizes and areal densities are formed, uniformly decorating the inner and outer walls from tube top to tube bottom. The photocatalytic activity for H2 evolution strongly depends on the size and density of Pt nanoparticles, driven by the number of ALD cycles. We show that, for SP NTs, a much higher photocatalytic performance can be achieved with significantly smaller Pt nanoparticles (i.e. for fewer ALD cycles) compared to CP NTs.
Keywords: photocatalysis; anodization; atomic layer deposition; platinum; spaced TiO2 nanotubes